Ferrous mineral enhanced anaerobic treatment of landfill leachate. Issue 24 (16th December 2016) - Zhang, Xun; Yue, Zheng-Bo; Wang, Jin; Wang, Hua-Ming; Chen, Tian-Hu
ABSTRACT: Addition of inorganic materials is one of the effective methods to improve the methane production yield from wastewater and organic biomass. In the treatment of landfill leachate, the anaerobic digestion process is one of the essential steps. In the current study natural ferrous minerals of iron sulfide and iron oxides were added into the anaerobic digester, which was expected to improve the digestion efficiency of leachate and methane yields. Results confirmed that the addition of minerals was feasible for the anaerobic treatment of leachate. Chemical oxygen demand (COD) removal efficiency in the pyrrhotite dosed reactor achieved a maximum value of 85%; meanwhile, it was only about 60% in the control. A higher methane yield was also achieved in the mineral dosed reactors and CO2 production was effectively reduced compared with the control. The promotion effect could be attributed to the adsorption and conductive characteristic of the minerals.